2012
DOI: 10.5698/1535-7511-12.5.184
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in Alzheimer Disease: Clinical and Epidemiological Data

Abstract: Epilepsy and AD are common neurologic disorders for which increasing age is a common and well-established risk factor (1, 2). The potential relation between these two disorders has been supported by experimental and clinical data. From a clinical aspect, patients with AD have an increased risk of developing seizures and epilepsy; thus AD may be an important cause of epilepsy in the elderly. AD and other neurodegenerative conditions represent the presumed etiology for 10% of new onset epilepsy in patients older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 47 publications
1
99
0
5
Order By: Relevance
“…The possible association of epileptic activity to Alzheimer's disease (AD) has been reported by means of animal and clinical studies (Palop and Mucke, 2009;Pandis and Scarmeas, 2012). From the clinical perspective, it has been shown that the incidence of unprovoked seizures in patients with AD is 6 to 10 times more common than age-matched healthy adults (Hauser et al, 1986;Hesdorffer et al, 1996;Hommet et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…The possible association of epileptic activity to Alzheimer's disease (AD) has been reported by means of animal and clinical studies (Palop and Mucke, 2009;Pandis and Scarmeas, 2012). From the clinical perspective, it has been shown that the incidence of unprovoked seizures in patients with AD is 6 to 10 times more common than age-matched healthy adults (Hauser et al, 1986;Hesdorffer et al, 1996;Hommet et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…If indeed the observed miR-211 elevation in the Alzheimer's entorhinal cortex relates to the disease pathophysiology, it may suggest an explanation to the greater risk for unprovoked seizures in early onset patients and those with more severe disease (66), where miR-211 increases would prove insufficient in avoiding seizures. This expression change, not seen in temporal lobe samples, may relate to the prominent cholinergic innervation of the entorhinal cortex by the medial septum.…”
Section: Discussionmentioning
confidence: 99%
“…This is possible in more than50% of the patients. Stroke or a history of stroke not only predisposes elderly patients to develop seizures but also occurrence of unprovoked seizures may increase the risk of subsequent development of stroke in elderly individuals [17] .…”
Section: Eegmentioning
confidence: 99%